Prevalence, risk factors, and outcomes of obstructed labor at the University of Maiduguri Teaching Hospital, Maiduguri, Nigeria - Babagana Bako; Emmanuel Barka; Abubakar A Kullima (Sahel Medical Journal, 2018)
Introduction: Obstructed labor is a common cause of feto-maternal morbidity and mortality in Maiduguri, Nigeria. This study aimed to determine the prevalence, causes, risk factors, and outcome of obstructed labor at the University of Maiduguri Teaching Hospital (UMTH). Materials and Methods: This was a retrospective observational study of all cases of obstructed labor managed from January 2012 to December 2014 at the UMTH, Maiduguri, Nigeria. For each case, the next woman who delivered without obstruction was used as a control. Data were analyzed for sociodemographic variables, labor, delivery and postdelivery events using SPSS version 20.0. The Chi-square test and odds ratio (OR) were used and statistical significance set at P < 0.05. Results: The prevalence of obstructed labor was 2.13%. Cephalopelvic disproportion, persistent occipitoposterior position, and malpresentation were seen in 65.37%, 16.58%, and 11.71%, respectively. The risk factors were teenage pregnancy (χ2: 26.96, P < 0.0001, OR: 4.44, 95% confidence interval [CI]: 2.45–8.05), nulliparity (χ2: 50.70, P < 0.0001, OR: 4.63, 95% CI: 2.99–7.15), illiteracy (χ2:53.91, P < 0.0001, OR: 5.26, 95% CI: 3.31–8.33), and unbooked status (χ2: 113.26, P < 0.0001 OR: 11.9, 95% CI: 7.24–19.61). Complications were observed in 37.56% of the women with obstructed labor. The common morbidities were wound sepsis, ruptured uterus, and puerperal sepsis, seen in 16.59%, 13.17%, and 7.81%, respectively. The case fatality rate was 0.98% and perinatal mortality was 34.15%. Conclusion: Obstructed labor is common in Maiduguri. We recommend amelioration of the risk factors through advocacy, girl child education, and public enlightenment on the need for antenatal care and hospital delivery, identification, and referral of high-risk patients.